Nose-to-brain delivery of lacosamide, levetiracetam and zonisamide and the impact of BCRP efflux: an in vitro/in vivo approach. - Gonçalves, Joana Carrapiço (2022)
Tese de Doutoramento em Ciências Farmacêuticas apresentada à Faculdade de Farmácia da Universidade de Coimbra.